No Relation between Psoriasis and Renal Abnormalities: A Case-Control Study - Zohreh Tehranchinia; Esmat Ghanei; Nahid Mohammadi; Masoud Partovi-Kia; Hoda Rahimi; Nikoo Mozafari (The Scientific World Journal)
Multiple observational studies have demonstrated that psoriasis is associated with nephropathy; however, the renal involvement in psoriasis remains largely a matter of debate. The current study was designed to investigate if psoriatic patients are at increased risk of renal abnormalities, in absence of any other comorbidities. Forty patients (11 women, 29 men, mean age 44.9 ± 15.45 years) with moderate to severe chronic plaque type psoriasis who were not under systemic therapy and 40 age- and gender-matched control subjects were enrolled in the study. Patients and controls with history of diabetes, hypertension, and chronic renal disease were excluded. Urinalysis by dipstick and microscopic evaluation and 24 h proteinuria and albuminuria were measured in all patients and controls. Patients with psoriasis and controls were not significantly different with respect to the prevalence of abnormal urinalysis (7.5% versus 5%, P = 1.0), mean 24 h proteinuria (70.40 ± 24.38 mg/24 h versus 89.40 ± 26.78 mg/24 h, P = 0.30), and albuminuria (14.15 ± 8.12 mg/24 h versus 16.62 ± 8.21 mg/24 h, P = 0.18). The presence of abnormal urinalysis was not more common in patients with psoriasis than in controls. Our study demonstrated that psoriatic patients without any other comorbidities are not at increased risk of kidney disease.